Giant myxoid liposarcoma of descending mesocolon origin - Uslukaya, Omer; Taskesen, Fatih; Aliosmanoglu, Ibrahim; Arikanoglu, Zulfu; Gul, Mesut; Dusak, Abdurrahim (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Liposarcomas are one of the most common primary lesions of the retroperitoneal region. They rarely exhibit intra-abdominal location. Because the symptoms emerge later on, they often remain unnoticed until they grow large. Our aim in this paper is to present a case of myxoid liposarcoma of descending mesocolon origin, 40 cm wide and weighing 7000 g, seen in a 47-year-old male patient. No cases at this weight and radius, originating from descending mesocolon, belonging to the myxoid sub-type, were found in our literature scan.